A Cross-Sectional Survey on Professionals to Assess Health Needs of Newly Arrived Migrants in Spain - Núria Serre-Delcor; Inés Oliveira; Ruben Moreno; Begoña Treviño; Eva Hajdók; Esperanza Esteban; Adrià Murias-Closas; Abdallah Denial; Stella Evangelidou (Frontiers Media S.A., 2021)
Heightened conflicts and lack of safety due to reasons related to economic, social, ethnic, religious, sexual orientation, political, or nationality matters have increased migratory movements during the last, few decades. Unfortunately, when migrants arrive in new territories, they can face many barriers. For example, in Spain, some migrants have difficulties in accessing health services. The main objective of this study was to describe, from the perspective of social and healthcare professionals, health needs and barriers faced among migrants who recently arrived in Spain when accessing the health system. To accomplish this aim, we carried out a cross-sectional descriptive study using a newly created self-administered questionnaire. Statistical analysis was done using the SPSS 23.00® program. Survey collection was from April 2018 to October 2018, and the cohort comprised a total of 228 professionals. Most participants were females (76%), with an average age of 35 years [interquartile range (IQR) 29.8-43.0]. The most represented profession in the cohort was physician (48%), followed by social care professionals (32%), nursing (11%), and other (8%). Of these individuals, 61% stated having either little or limited knowledge of international migrant health rights, and 94% believed migrants must overcome barriers to receive health services. The four most reported barriers were as follows: language, cultural differences, administrative issues, and fear of being undocumented. Additionally, by order of importance, professionals viewed mental health disorders and infectious diseases as the most common contributors to disease burden in this group. The four most popular strategies implemented by professionals to improve healthcare access further for migrants included intercultural competency training for professionals; access to community health agents; access to translators; and development of health system navigation skills among those newly arrived. Study results suggest that governments should make greater efforts to provide social and healthcare professionals with more effective tools that overcome communication barriers and cultural competence training modules.